Balancing Entertainment, Cost, and Educational Strength: A Design Framework for Medium-Coupling Educational Games - Atmaja, Pratama Wirya; Sugiarto, Sugiarto (Universitas Muhammadiyah Malang, 2021)
Games are powerful tools for teaching and learning, especially in the age of Education 4.0. The rapid growth of educational games is hindered by various problems, including their development cost. The medium coupling approach, which allows an educational game to be both engaging and economical, is one potential solution to the problem; unfortunately, it has received only sporadic attention. This study aims to explore the matter of designing medium-coupling educational games through a design framework. The framework dissects an educational game’s game content and educational content into parts to be interconnected. We applied the framework to design and develop an educational role-playing game (RPG). Sixty first-year Informatics students tested the game, which presented three learning topics with different characteristics. A post-test questionnaire’s results validate the game’s entertainment and educational values while also uncovering how it works under different learning contents. A discussion with the participants gathered insightful suggestions and critiques, which, together with the questionnaire’s results, are synthesized into design principles for medium-coupling games. We conclude that the framework is useful for creating games that are entertaining, educational, and cost-efficient.